Analysis of Volatile Constituents from Abelmoschus manihot by GC-MS - Wang, Yan; Wang, Bao-Hua; Lu, Bing; Li, Ping; Yang, Bei-Bei; Ji, Wen-Qin; Meng, Qing-Qing (Asian Journal of Chemistry, 2015)
The volatile constituents from Flos Abelmoschus manihot were extracted from Flos Abelmoschus manihot by steam distillation and analyzed by GC-MS. A total of 47 compounds were successfully identified. The major components of the volatile constituents in Flos Abelmoschus manihot included hexadecane, 2,6,10,14-tetramethyl-hexadecane (37.83 %), pentacosane (13.49 %), 9-octyl-heptadecane (9.78 %), cedrol (3.07 %), 9,12,15-octadecatrienoic acid, methyl ester, (Z,Z,Z)- (2.79 %), tetratetracontane (2.78 %), cyclotetracosane (2.61 %) and hexadecanoic acid, methyl ester (2.32 %). The major components in volatile constituents were hydroxy compounds, acyclic alkanes, other arenes and sesquiterpenes.